A combined pressure regulation technology with multi-optimization of the entrainment passage for performance improvement of the steam ejector in MED-TVC desalination system. (15th May 2019) - Tang, Yongzhi; Liu, Zhongliang; Li, Yanxia; Shi, Can; Lv, Chen
Abstract: Steam ejector as an energy-saving unit is of critical importance to the overall performance of MED-TVC desalination system. In this study, a combined pressure regulation solution is proposed to dredge the blocked entrained flow and alleviate the high-pressure effect simultaneously for multiple optimization of the entrainment passage flow field. The systematic analysis and investigation mainly concentrate on the feasibility verifications of the combined pressure regulations, and the performance comparisons between the combined and single pressure regulation schemes under various operating conditions. The results reveal that the throat-combined pressure regulation would simply lose efficacy, the diffuser- and multi-combined pressure regulations could achieve a similar multiple optimization that the alleviation effectiveness remains almost steady and the dredging effectiveness enhances continually as the back pressure decreases. Moreover, there is an optimum combination among the pressure regulation schemes, by which a most significant entrainment ratio improvement could be achieved, as high as 28.75% in the present simulations covered range. To be specific, TMCE pressure regulation could be selected if the ejector operates under the design condition, and for the off-design conditions, multi-combined pressure regulation should be adopted if the back pressure not exceeds its critical value, otherwise, CMCE pressure regulation is the best choice. Highlights: The low-pressure potentials could regulate the high-pressure and blocked regions. Combined pressure regulation is proposed to improve the entrainment performance. There is an optimum combination of various pressure regulation schemes. The multiple optimization effect could be achieved under off-design conditions.